Childhood Adversity, Resilience, and Mental Health: A Sequential Mixed-Methods Study of Chinese Young Adults. Issue 19 (October 2021) - Ho, G. W. K.; Chan, A. C. Y.; Shevlin, M.; Karatzias, T.; Chan, P. S.; Leung, D.
Resilience is a key health protective factor for those with adverse childhood experiences (ACEs), but little research has explored how it manifests in early adulthood or across cultures. The purpose of this study was to generate a fuller understanding of resilience and its contribution to the relationships between mental health problems and ACEs among Chinese young adults in Hong Kong. Using a sequential explanatory mixed-methods design, 433 Chinese young adults aged 18 to 24 years were surveyed online to examine the relationships between ACEs, resilience, and mental health problems (depression, anxiety, maladjustment, and posttraumatic stress symptoms). Among them, 34 participants with ACEs were purposively selected and interviewed to explore cultural factors that influenced their resilience. Quantitative data were analyzed using multiple hierarchical regression analyses; qualitative data were analyzed using a qualitative descriptive approach. Higher cumulative ACE exposure was associated with higher severity of adjustment disorder and odds for screening positive for posttraumatic stress disorders, but not for symptoms of depression or anxiety. Resilience significantly contributed to explaining variances across all mental health outcomes over and beyond ACEs and in a protective fashion. Four themes emerged from qualitative interviews: (a) Privacy, emotional restraint, and "saving face" ; (b) Conforming to preserve harmony ; (c) A will to excel ; and (d) Viewing adversity as a matter of luck . These findings suggest Chinese young adults' resilience was influenced by cultural norms of restraint, conformity, competition, and superstition. The present study provides a model for future studies using a mixed-methods design to deeply examine resilience among younger people exposed to early adversities within sociocultural, historical, or geographical contexts.